2010
DOI: 10.1093/sleep/33.5.631
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Regulation of Sleep and the Sleep EEG under Constant Sleep Pressure in the Rat

Abstract: In rats, the daily modulation of REM sleep is less pronounced compared to NREM sleep and waking. In contrast to SWA, activity in higher frequencies (7-25 Hz) in the NREM sleep EEG have an endogenous circadian origin and are not influenced by sleep homeostatic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…This measure also showed a clear but reduced diurnal rhythm on each day of CSR, with an amplitude about half of that shown on the baseline day (data not shown). This reduction of daily rhythmicity in NREMS delta power, despite the preservation of the daily rhythmicity of NREMS and other sleep measures throughout CSR days, is consistent with the predominance of homeostatic processes over circadian processes for this sleep intensity measure (57,66).…”
Section: Sleep Patterns During Csrsupporting
confidence: 76%
See 3 more Smart Citations
“…This measure also showed a clear but reduced diurnal rhythm on each day of CSR, with an amplitude about half of that shown on the baseline day (data not shown). This reduction of daily rhythmicity in NREMS delta power, despite the preservation of the daily rhythmicity of NREMS and other sleep measures throughout CSR days, is consistent with the predominance of homeostatic processes over circadian processes for this sleep intensity measure (57,66).…”
Section: Sleep Patterns During Csrsupporting
confidence: 76%
“…Consistent with these results, Yasenkov and Deboer (66,67) reported that circadian variations in EEG frequencies in the 7-to 25-Hz range during NREMS were maintained during repeated 2 h SOs in constant darkness. These findings suggest that deltarange EEG activity may be under more rigorous homeostatic control, with limited time-of-day influence, while the higherfrequency EEG activity may be modulated by both homeostatic and time-of-day influences.…”
Section: Sleep Patterns During Csrsupporting
confidence: 58%
See 2 more Smart Citations
“…Without discriminating the sleep/wake status, especially during the baseline period, the sleep or waking transitions themselves may produce larger fluctuations than test stimulations such as exercise. EEG activities also vary with the circadian rhythm (Grasing and Szeto 1992;Yasenkov and Deboer 2010); thus we only selected and compared the waking baseline values captured during the latest 3 h of the dark period.…”
Section: Discussionmentioning
confidence: 99%